25 Organ donation in emergency departments: an analysis of best practice. Issue 12 (23rd November 2017) - Empson, Katja; Beale, Sarah; Kerr, Jacques; Gardiner, Dale
Abstract : Introduction: The 2015 RCEM End of Life Care best practice guideline highlighted the need for organ and tissue donation to be a usual part of end of life care in the Emergency Department (ED). NICE guideline states that all deaths meeting defined clinical triggers in the ED (in practice – mechanical ventilation, plan to withdraw life sustaining treatment, death expected) should prompt timely referral to organ donation services. Any family discussion in the ED regarding organ donation should be held collaboratively with a specialist nurse for organ donation (SNOD). What is the evidence in UK EDs that this is always the case? Methodology: The NHS Blood and Transplant Potential Donor Audit, carried out by specialist nurses in organ donation, audits every death aged 80 years and under in UK Emergency Departments and Intensive Care Units. Data from the Potential Donor Audit was analysed and compared across the 12 Regional NHSBT teams. Results: Almost all deceased donors in the UK are admitted to hospital via an Emergency Department (ED). The number of patients dying in UK EDs aged under 80 years of age and under (1 st April 2015 to 31 st March 2016) is variable across the country and not directly correlated with population. Patients dying in ED, who meet criteria for referral is equally variable across the UK (Range 1% Scotland – 3.9% Eastern). PDA data (1 April 2016 – 31 March 2017) reveals that 284 patients died in ED meeting referral criteria but only 47% were referred (Range 22%–65% across the 12 regions). Longer 4 year analysis (1 st April 2012 – 31 st March 2016) demonstrated that up to 16% of these patients are on the Organ Donor Register. Of the 125 families approached in the ED (1 April 2016 – 31 March 2017) only 67% involved a SNOD (Range 0%–100% across the 12 regions). Discussion: In 2017, with the endorsement of RCEM, NHS Blood and Transplant published Organ Donation and the Emergency Department: A Strategy for Implementation of Best Practice. The strategy promotes identification and referral of potential organ donors in the emergency department and collaborative approach of their families when withdrawal of treatment is planned in the Emergency Department. Most importantly it is emphasised that organ donation should be firmly established as a usual part of end of life care irrespective of the location of the patient.